Heritage Tourism in Island of Martinique (West Indies). A case of study of Le Tour des Yoles and the Festive Nautical Heritage - Olivier Dehoorne; Dorina C. Ilies; Alexandru Ilies; Sopheap Theng; Corina Tatar (Études Caribéennes)
Tourism in the Caribbean islands is approached mainly under the prism of the beach, the sun, with a whole series of clichés that forget the indigenous populations, their daily life, their culture and their tradition which make their identity. The tourist industry imposes itself, denying everyday life. Our study is devoted to understanding a nautical festival in Martinique (West Indies). This festival, which is part of the history of the island, endures in culture and identity. It becomes a major festive event for the destination, without being planned as a "tourist attraction". It is a tourist event that is part of a cultural continuity between the Martinicans of Martinique and the diaspora returning to the country for the holidays.